2022
DOI: 10.1021/acs.joc.2c01574
|View full text |Cite
|
Sign up to set email alerts
|

Benzylic C(sp3)–H Bonds Play the Dual Role of Starting Material and Oxidation Inhibitor for Hydrazides in the Electrochemical Synthesis of Hydrazones

Abstract: The electrooxidation of benzylic C(sp 3 )−H bonds to produce hydrazones as an alternate for conventional pathways has an enormous dignity. Under the aegis of electricity, instead of hazardous metal catalysts and external oxidants, we unveil an electrochemical process for electrooxidation of various benzylic C(sp 3 )−H bonds in aqueous media in all pH ranges that subsequently produce hydrazones with further reactions. This electrooxidative reaction strategy provides an acceptable condition for synthesizing hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…31, 145.97, 138.32, 133.18, 131.92, 129.79, 129.54, 128.51, 127.67, 125.73 (q, J = 3.9 Hz), 124.08 (q, J = 272.2 Hz). 11 According to the general procedure, 4-chlorobenzaldehyde (281 mg, 2.0 mmol) gave 4f (160 mg, 0.62 mmol, 62% yield, white solid) after column chromatography (n-hexane/EtOAc, 4:1); mp 166-167 °C. FTIR (neat): 1673, 3439 cm -1 .…”
Section: (E)-n′-(4-(trifluoromethyl)benzylidene)benzohydrazide (4e)mentioning
confidence: 99%
See 1 more Smart Citation
“…31, 145.97, 138.32, 133.18, 131.92, 129.79, 129.54, 128.51, 127.67, 125.73 (q, J = 3.9 Hz), 124.08 (q, J = 272.2 Hz). 11 According to the general procedure, 4-chlorobenzaldehyde (281 mg, 2.0 mmol) gave 4f (160 mg, 0.62 mmol, 62% yield, white solid) after column chromatography (n-hexane/EtOAc, 4:1); mp 166-167 °C. FTIR (neat): 1673, 3439 cm -1 .…”
Section: (E)-n′-(4-(trifluoromethyl)benzylidene)benzohydrazide (4e)mentioning
confidence: 99%
“…(E)-N′-(4-Methylbenzylidene)benzohydrazide (4a) 11 According to the general procedure, 4-methyl-benzaldehyde (240 mg, 2.0 mmol) gave 4a (190 mg, 0.80 mmol, 80% yield, white solid) after column chromatography (n-hexane/EtOAc, 4:1); mp 188-190 °C. FTIR (neat): 1674, 3440 cm -1 .…”
Section: Benzoyl Hydrazones From Benzoylpyrrolidin-2-one and Various ...mentioning
confidence: 99%
“…Ding et al reported a photocatalytic pathway using methylene blue and blue LED light to synthesize acyl hydrazones from acyl hydrazide and styrene (Scheme 1b). [16] Contemporary methodologies also use alcohols as a source of aldehydes, generated in situ, which then couple with acyl hydrazides when catalyzed by electrochemical means [17] or metal complexes like Fe/Ru complex [18] (Scheme 1c). All of these traditional and contemporary ways of acyl hydrazone synthesis rely on two reacting components, which often require special precautions, inert atmosphere, or prior preparation of expensive catalysts or special reaction set-up (in case of photocatalysis).…”
Section: Introductionmentioning
confidence: 99%